The influence of advice on a service purchase decision and the role of personality in this effect - Fernandes, Madalena de Ornelas (2021)
The influence of others in human behavior is part and parcel of everyday life. In a service purchase, where the outcome is uncertain and contingent on different personal experiences, the purchasing decision may be more difficult, making individuals more likely to be influenced by advice. However, given we are all different and personality is one of the main ways in which we differ, personality may explain some of the variation in susceptibility to advice. This dissertation studies the influence of advice in the price consumers are willing to pay for a service. Additionally, this study investigates the role of specific personality traits (Agreeableness, Conscientiousness and Neuroticism) in advice influence on the final decision. Moreover, I investigate if there is a difference in advice influence according to the way in which advice is received, whether advice is solicited or unsolicited, and how the aforementioned personality traits moderate this effect. Results show that advice positively influences participants’ final decision, irrespective of the way in which advice was received. Results also revealed that Conscientiousness significantly decreased advice influence, Neuroticism significantly increased it, and Agreeableness was not significantly related to advice influence. However, when controlling for age and gender, this study found that these effects were no longer significant. Finally, this research found no evidence of moderation by personality traits on the relationship between advice influence on the final decision and the way advice was received.